2010
DOI: 10.1007/s11262-010-0481-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid differentiation of vaccine strain and Chinese field strains of transmissible gastroenteritis virus by restriction fragment length polymorphism of the N gene

Abstract: A strain of transmissible gastroenteritis virus (TGEV), designated H16, was isolated in PK-15 cells and passaged serially to level 165. Vaccines based on passages 155-165 in cell cultures are available commercially as vaccines for the prevention and control of infections with TGEV in China. Nucleoprotein (N) sequences of the virus at passages 155 and 165 were aligned and compared using a computer software program. The suitability of restriction fragment length polymorphism (RFLP) analysis for differentiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The results indicated that PEDV has a high prevalence rate in pig herds. TGEV was also detected by RT-PCR [16] in our lab, and the overall detection rate was 29.12% in clinical samples. Two other research groups in China reported that 40.8% (20 of 49) and 22.73% (5 of 22) sow milk samples were positive for PEDV in 2011 [5,6], and hypothesized that sow milk could represent a possible route for the vertical transmission of PEDV from sow to suckling piglets [5].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that PEDV has a high prevalence rate in pig herds. TGEV was also detected by RT-PCR [16] in our lab, and the overall detection rate was 29.12% in clinical samples. Two other research groups in China reported that 40.8% (20 of 49) and 22.73% (5 of 22) sow milk samples were positive for PEDV in 2011 [5,6], and hypothesized that sow milk could represent a possible route for the vertical transmission of PEDV from sow to suckling piglets [5].…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of rapid, sensitive, and cost-effective diagnostic assays for detecting TGEV is highly desirable. In addition to conventional virus isolation, there are other diagnostic methods available for TGEV, for example, Multiplex PCR and multiplex RT-PCR, real-time RT-PCR, restriction fragment length polymorphism, microarray hybridization assay, and blocking ELISA [8,21,28,36,40]. Although these methods are effective, they may require either high-precision instruments or complicated procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, occasional reports of TGEV-specific seropositivity (Elvander et al, 2000;Brendtsson et al, 2006;Roic et al, 2012) and even sporadic outbreaks in different parts of the world (Pritchard et al, 1999;Kim et al, 2000;Miyazaki et al, 2010;Wang et al, 2010) indicate that TGE cannot be neglected, as the virus is still present in pig herds, although mostly without clinical manifestations.…”
Section: Lőrincz Et Almentioning
confidence: 99%